2012
DOI: 10.1371/journal.pone.0036525
|View full text |Cite
|
Sign up to set email alerts
|

DR6 as a Diagnostic and Predictive Biomarker in Adult Sarcoma

Abstract: BackgroundThe Death Receptor 6 (DR6) protein is elevated in the serum of ovarian cancer patients. We tested DR6 serum protein levels as a diagnostic/predictive biomarker in several epithelial tumors and sarcomas.MethodsDR6 gene expression profiles were screened in publically available arrays of solid tumors. A quantitative immunofluorescent western blot analysis was developed to test the serum of healthy controls and patients with sarcoma, uterine carcinosarcoma, bladder, liver, and pancreatic carcinomas. Chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…Our results as well correlate with Yang et al [26] who detected overexpression (125%) of DR6 mRNA in patients suffering from ductal invasive carcinoma.…”
Section: Resultssupporting
confidence: 92%
“…Our results as well correlate with Yang et al [26] who detected overexpression (125%) of DR6 mRNA in patients suffering from ductal invasive carcinoma.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, B-cells lacking TNFRSF21/DR6 show the increased proliferation rate and cell survival upon mitogenic stimulation [25]. However, this gene is highly expressed in many tumor cell lines and tumor samples [25,26]. Thus, the role of TNFRSF21/DR6 as an apoptosisinducing receptor is less clear and perhaps cell type dependent and needs further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Recently it was also shown that TNFRSF10B/TRAILR2 inhibits maturation of the microRNA let-7 and increases proliferation of pancreatic cancer cell lines and other tumor cells [22]. Moreover, the expression of TRAIL receptors is greatly elevated in many cancer types, suggesting that tumors benefit from the expression of these receptors [25,26]. To date, the majority of studies on експериментальні роботи…”
Section: Fig 3 Effect Of Glucose Deprivation Condition On the Exprementioning
confidence: 99%
See 2 more Smart Citations